1993
DOI: 10.1002/ccd.1810300106
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angioplasty through 4 french diagnostic catheters

Abstract: In 50 consecutive patients subjected to coronary angioplasty immediately following a 4 French (F) diagnostic study, the technical feasibility and economical aspects of angioplasty through 4F catheters of 54 lesions were assessed. The patients were selected, but multiple, eccentric, and long lesions were not a priori excluded. 4F diagnostic catheters (Cordis), and fixed-wire dilatation catheters (Ace, Scimed) were used in all cases. The procedure was successful in 43 lesions (80%) using 4F catheters. For 11 ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The theoretical advantages of smaller catheters include reduced local vascular complications, decreased coronary pressure damping, less blood loss during PTCA, and facilitation of early ambulation after the procedure [1][2][3][4][5][6][7][8]10,11]. The potential disadvantages include catheter softening, resulting in inadequate backup to cross tortuous, distal, or calcified lesions; inability to accommodate large devices, such as intracoronary stents, perfusion catheters, and atherectomy devices; and coronary artery dissection due to increased manipulation required to secure adequate backup.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical advantages of smaller catheters include reduced local vascular complications, decreased coronary pressure damping, less blood loss during PTCA, and facilitation of early ambulation after the procedure [1][2][3][4][5][6][7][8]10,11]. The potential disadvantages include catheter softening, resulting in inadequate backup to cross tortuous, distal, or calcified lesions; inability to accommodate large devices, such as intracoronary stents, perfusion catheters, and atherectomy devices; and coronary artery dissection due to increased manipulation required to secure adequate backup.…”
Section: Introductionmentioning
confidence: 99%
“…However, advances in equipment, including reductions in device and catheter caliber, have allowed for coronary angioplasty procedures to be performed through 4-6 Fr catheters and sheaths [37][38][39][40]. Several retrospective studies have identified associations between sheath size and access site complications [5,7,8], although other studies have not found any association [6,10].…”
Section: Bleeding Complications With Early Invasive Strategymentioning
confidence: 96%
“…This preference for 6F G-Cs is growing, as these advantages have been supported by preliminary studies and large registries which clearly demonstrate that the vascular complication rate is related to G-C Size [6][7][8]. In order to reduce these bleeding complications and permit earlier hospital discharge, it would be tempting to perform coronary angioplasty with smaller G-Cs, but this might result in deleterious outcomes, because of a lack of angiographic control and inability to use many bailout devices [9,10]. In order to diminish the size of the vascular puncture site while keeping the large and safe lumen of the 6 French G-C, we have developed a new device called the INTRUC, to introduce the 6F G-C percutaneously without need of an external sheath (INTRUC stands for Introducing-catheter).…”
Section: Introductionmentioning
confidence: 98%